INTEGRATING QUR’ANIC INSIGHTS AND ZOOLOGICAL KNOWLEDGE IN ISLAMIC RELIGIOUS EDUCATION: IMPLICATIONS FOR BIOLOGY LEARNING IN ISLAMIC SCHOOLS AND MADRASAS - Hafiz Aon Muhammad; Maria Ashraf Dogar (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2026)
This study examines how Qur’anic insights into animal life and contemporary zoological knowledge can be integrated into Islamic Religious Education (PAI), particularly biology-related learning in Islamic schools and madrasas. Rather than treating scientific knowledge as a means of validating Qur’anic verses, the study adopts an integrative educational perspective in which Qur’anic teachings provide ethical, spiritual, and reflective dimensions for understanding biological phenomena. Using a qualitative and comparative approach, selected Qur’anic verses concerning animal communities, domesticated animals, honeybees, ants, biodiversity, and ecological relationships were analyzed alongside relevant zoological literature and studies on Qur’an–science integration in Islamic education. The findings indicate that Qur’anic references to animals can be transformed into contextual learning resources that connect biological concepts with Islamic values, including stewardship, gratitude, responsibility, biodiversity conservation, and reflection on creation. The study further identifies several possible applications in PAI and integrated science learning, including contextual learning, inquiry-based learning, interdisciplinary learning, and the development of Qur’an-integrated teaching materials. These approaches can help students understand zoological concepts while simultaneously developing ethical and spiritual awareness of human relationships with animals and the environment. The study therefore argues that Qur’an–zoology integration should be positioned not primarily as scientific verification of revelation, but as an educational framework for developing meaningful, contextual, and value-oriented learning in Islamic schools and madrasas. Keywords: Qur’anic integration, Islamic Religious Education, PAI, zoology education, Islamic schools, madrasas, integrated learning.